PENGARUH PENYULUHAN TEKNIK MENYUSUI TERHADAP PRAKTIK MENYUSUI PADA IBU MENYUSUI DI KLINIK PRATAMA HANUM TANJUNG MULIA MEDAN - Mayang Wulan; Ani Deswita Chaniago; Nurjannah - (Universitas Prima Indonesia, 2024)
Breastfeeding is an ideal way for mothers to give love to their children and the best way to fulfill the baby's nutrition. Breastfeeding technique is a way of giving breast milk to a mother to a baby. The study aimed to determine the average difference before and after counseling on correct breastfeeding techniques at the Pratama Hanum Tanjung Mulia Clinic, Medan City. This type of research is a quasi-experiment with a one-group pre and post-test design. The population in the study was 20 breastfeeding mothers who had babies aged 0-12 months. The sampling technique is purposive sampling. Data were analyzed by carrying out normality tests and Wilcoxson tests. Results: Before the counseling was carried out, the majority of breastfeeding techniques were 12 people (60%), while 8 people (40%) had good breastfeeding techniques. After counseling, it was found that 2 people (10%) had poor breastfeeding techniques, while 18 mothers (90%) had good breastfeeding techniques. From the results of the analysis using the Wilcoxson test, a significant value of p = 0.002 < 0.05 was obtained. There is an influence of Breastfeeding Technique Counseling on Breastfeeding Practices for Breastfeeding Mothers at the Pratama Hanum Tanjung Mulia Clinic. It is recommended that health workers at the Pratama Hanum Tanjung Mulia Clinic, Medan City, be more effective in providing understanding to mothers about correct breastfeeding techniques. Keywords: Breastfeeding Techniques, Breastfeeding Practices, Breastfeeding Mothers